A ferramenta tecnológica da blockchain na atividade notarial: novos contornos para a segurança e a confiança nos tabelionatos - Lopes, Rossana Chassot (Universidade do Vale do Rio dos Sinos, 2021)
The present study aims to analyze the applicability of blockchain technology in notarial activity, given the revolutionary promise of replacing any intermediaries to carry out negotiations between sellers and buyers, through a trust protocol implemented in a self-sufficient and fraud-free process. The specific objective of the research is to verify the possibility of deploying a digital platform with the use of blockchain technology to store the notary's office collection, which guarantees greater security to the stored files and enables access to notarial acts, reinforcing the principle of publicity of notarial activity. The predominant method used in the study is the literature review and documentary research on the effects that blockchain technology exerts on notarial activity. For the elaboration of the dissertation, information was collected from books, articles and other bibliographic materials. Legislations that regulate the use of information technology in notarial activity were also studied, including provisions of the National Council of Justice and the General Court of Justice of the State of Rio Grande do Sul. Activity provided for in the Federal Constitution and regulated by Federal Law n. 8.935/94, has as its primary task to provide certainty and security to the legal acts of individuals and public entities through their public faith. Currently, the notarial activity has been expanding its responsibilities, working with the combat of money laundering crimes, as well as the resolution of disputes through mediation and conciliation. More recently, notaries have been working in the digital sphere, following the evolution of virtual business media. In a second part of the work, the study turns to blockchain technology, seeking to conceptualize it and explain its main characteristics. In the final chapter, we sought to deepen the aspect of trust provided by the notarial activity and the blockchain, in order to demonstrate the points of convergence between them, in addition to presenting the possibility of adding a technological resource to the notarial activity in order to enhance the provision of the service. As a final result of the work, it is suggested the expansion of services provided by the Notarial Center for Shared Electronic Services - CENSEC - established by Provision No. 18, of August 28, 2012, of the National Council of Justice, with the use of blockchain technology capable of store the collection of the notary public's office and provide access to the notarial acts by other notary offices and other bodies to facilitate the conference of data and the exchange of information.
Keywords: Atividade notarial; Tecnologia blockchain; Segurança; Confiança; Notarial activity; Blockchain technology; Safety; Trust; ACCNPQ::Ciências Sociais Aplicadas::Direito